Gaya hidup "prihatin" dalam ajaran Serat Wulung Reh - Muchson AR, Muchson AR (Jurnal Civics: Media Kajian Kewarganegaraan, 2010)
This article is adopted from the research on the contents of character education values in the book of ’Serat Wulang Reh’, written by Paku Buwana IV (1768-1820). The value of character education revealed is about a distinctive lifestyle which is in a Java terminology called "˜laku prihatin’. The research employs the content analysis method. The data collected from the content of the book are constructed into two units; syntactical and thematic one. Analysis of data in this study includes descriptive analysis and inferential analysis. The result of study shows that ’Serat Wulang Reh’ teaches "˜laku prihatin’. Those include reducing of eating and sleeping, appliance of simple and non excessive style of living, practice of self suppression, and feel of sufficiency with the existing livelihood. "˜Laku prihatin’ in a high or extreme level is in the form of habituation of the sufferance and of ascetism practices.